Myasthenia Gravis Disease Mechanism and Immunointervention - Christadoss, Premkumar (Springer Netherlands, 2000)
Autoimmune myasthenia gravis (MG) is a classical autoimmune disease, for which the target antigen, nicotinic acetylcholine receptor, has been cloned, sequenced and biochemically characterized. Antibodies to acetylcholine receptors destroy acetylcholine receptor at the neuromuscular junction, thus leading to defective neuromuscular transmission, muscle fatigue, and weakness. In the last few years, rapid advances have been made in unraveling the cellular and molecular mechanisms involved in the pathogenesis of MG, both in the animal model, experimental autoimmune MG (EAMG), and in human MG. Significant advances are being made in characterizing the cells and molecules involved in the autoimmune response to the acetylcholine receptor (AChR). These advances are leading to the development of specific methods of immunointervention in EAMG.